Determination of SB2 masses and age: introduction of the mass ratio in the Bayesian analysis. Issue 3 (14th April 2018) - Giarrusso, M; Leone, F; Tognelli, E; Degl'Innocenti, S; Prada Moroni, P G
Abstract: Stellar age assignment still represents a difficult task in Astrophysics. This unobservable fundamental parameter can be estimated only through indirect methods, as well as generally the mass. Bayesian analysis is a statistical approach largely used to derive stellar properties by taking into account the available information about the quantities we are looking for. In this paper, we propose to apply the method to the double-lined spectroscopic binaries (SB2), for which the only available information about masses is the observed mass ratio of the two components. We validated the method on a synthetic sample of pre-main-sequence (PMS) SB2 systems showing the capability of the technique to recover the simulated age and masses. Then, we applied our procedure to the PMS eclipsing binaries Parenago 1802 and RX J0529.4+0041 A, whose masses of both components are known, by treating them as SB2 systems. The estimated masses are in agreement with those dynamically measured. We conclude that the method, if based on high resolution and high signal-to-noise spectroscopy, represents a robust way to infer the masses of the very numerous SB2 systems together with their age, allowing to date the hosting astrophysical environments.